2005
DOI: 10.7863/jum.2005.24.10.1347
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Breast Conditions in Childhood and Adolescence

Abstract: Knowledge of regular breast development and its variants is essential for the physician. Given knowledge of the sonographic appearance of physiologic breast development and specific lesions, breast sonography is most helpful in identifying and characterizing abnormalities and guiding further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 16 publications
0
32
0
4
Order By: Relevance
“…Moreover, the total number of malignant masses was higher among the menopausal women compared to those in the reproductive ages, which is similar to the results obtained by Mehrabani et al (Mehrabani et al, 2012). This might result from the protective effects of hormonal cycles against malignancies during the reproductive ages (Bock et al, 2005;Hartmann et al, 2005). In general, fibrocystic changes are highly prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the total number of malignant masses was higher among the menopausal women compared to those in the reproductive ages, which is similar to the results obtained by Mehrabani et al (Mehrabani et al, 2012). This might result from the protective effects of hormonal cycles against malignancies during the reproductive ages (Bock et al, 2005;Hartmann et al, 2005). In general, fibrocystic changes are highly prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fibroadenoma was most prevalent before menopause, which is corresponding with the results of other studies indicating fibroadenoma as the most common breast mass in young women. (Bock et al, 2005;Khanzada et al, 2009;Taj et al, 2009;AlRikabi and Husain, 2012) In general, fibroadenoma and fibrocystic changes are the most prevalent benign breast disorders (Sirous and EBRAHIMI, 2008) . In the present study, fibrocystic changes were shown to be the second most frequent breast disorder; such a way that it comprised 25% of the benign cases, with the mean age at occurrence being 36.7±10.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Gray-scale US is therefore the most important diagnostic tool (7,12) and the method of choice for confirming the presence of breast tissue and characterizing abnormalities (6).…”
Section: Discussionmentioning
confidence: 99%
“…This was revealed in a study conducted among 62 females aged 8 weeks to 20 years; the study was conducted using standard sonography. It is important for a specialist to have prior knowledge of the normal breast and its variants in order to be able to detect abnormalities [5]. Breast ultrasound plays a major role in the identification, diagnosis, and staging of breast cancer and the different soft-tissue structures in the breast have different echogenicities [10].…”
Section: Breastmentioning
confidence: 99%
“…Previous study states that breast development occurs in different phases of a woman's life [4]. The development of the mammary gland as a complex organ starts in the early phase of gestation with a steady change in shape, function and size from puberty to menopause [5][6]. Recent researches have added new knowledge about the anatomy of the breast which indicates fat in the breast to be hypoechoic and dark gray in color, while fibroglandular tissue is hyperechoic and white in gray-scale intensity [7].…”
Section: Introductionmentioning
confidence: 99%